Moderasi Beragama Berbasis Budaya dan Kearifan Lokal di Desa Sibolangit - Satria Ramadhan K. Telaumbanua; Mhd. Yadi Harahap; Ika Ramdhan Ningsih Aceh; Nurwinda Herman⁴; Wahyu Arli (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Religious modernization is the life of human beings related to the behavior of carrying out their religious teachings influenced by changes in political systems, religion, economics, psychology, science, advances in technology and information. Diversity includes differences in culture, religion, race, language, ethnicity, tradition and so on. In such a multicultural society, tensions and conflicts often occur between cultural groups and have an impact on the harmony of life. The purpose of this paper is to discuss the cultural diversity in the village of Sibolangit. The method requires multicultural understanding and awareness that respects differences, pluralism and the willingness to interact socially with anyone fairly. Religious moderation is needed in the form of minimizing violence in difference. The role of community leaders and the role of religious instructors is needed to socialize, develop religious moderation to the Sibolangit village community for the realization of harmony and peace. Keywords: Society, Compound, Social